2016
DOI: 10.1007/s10495-016-1295-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dynamics during cell cycling

Abstract: Mitochondria are the cell's power plant that must be in a proper functional state in order to produce the energy necessary for basic cellular functions, such as proliferation. Mitochondria are 'dynamic' in that they are constantly undergoing fission and fusion to remain in a functional state throughout the cell cycle, as well as during other vital processes such as energy supply, cellular respiration and programmed cell death. The mitochondrial fission/fusion machinery is involved in generating young mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
130
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(135 citation statements)
references
References 94 publications
2
130
0
3
Order By: Relevance
“…All these maintain mitochondrial and cellular functions. Collectively, these processes are referred to as mitochondrial dynamics [176,177]. The daily oscillations of mitochondria are believed to be dependent on the clock proteins Period1 and Period2 (PER1/2) since they are blunted in mice lacking these proteins [178].…”
Section: Melatonin Regulates Mitochondrial Dynamicsmentioning
confidence: 99%
“…All these maintain mitochondrial and cellular functions. Collectively, these processes are referred to as mitochondrial dynamics [176,177]. The daily oscillations of mitochondria are believed to be dependent on the clock proteins Period1 and Period2 (PER1/2) since they are blunted in mice lacking these proteins [178].…”
Section: Melatonin Regulates Mitochondrial Dynamicsmentioning
confidence: 99%
“…(Liesa & Shirihai, 2013;Mishra & Chan, 2016;Nasrallah & Horvath, 2014), cell cycle progression (Horbay & Bilyy, 2016;Mishra & Chan, 2014), aging (Sato, Nakada, & Hayashi, 2006;Sebastián, Palacín, & Zorzano, 2017;Seo et al, 2010), innate immunity (Mills, Kelly, & O'Neill, 2017;Pourcelot & Arnoult, 2014), cell death, and survival (Otera & Mihara, 2012;Sheridan & Martin, 2010;Suen, Norris, & Youle, 2008). In addition to its positive role in mitochondrial fission, Drp1 also resulted in mitochondrial translocation of E3-ubiquitin ligase Parkin leading to degradation of mitochondrial fusion protein Mitofusin 1.…”
mentioning
confidence: 99%
“…Mitochondrial fission is also regulated by posttranslational modifications of Drp1, such as phosphorylation . Phosphorylation of Drp1 at Ser‐616 by the cyclin‐dependent kinase 1 (CDK1)/cyclin B complex stimulates Drp1 activition and results in mitochondrial fragmentation . As studies have shown that Ca 2+ /calmodulin‐dependent protein kinases Iα and II promote phosphorylation of Drp1 at Ser‐600/616 and increase Drp1 translocation to mitochondria, respectively, whether CDK1/cyclin B‐mediated phosphorylation at Ser‐616 could also promote Drp1 translocation to mitochondria warranted further study.…”
mentioning
confidence: 99%